Sosialisasi Pentingnya BPJS Kesehatan dan Penggunaan Media Booklet “Celoteh” dalam Peningkatan Program Prolanis di Kelurahan Melebung - Arnila Melina; Faisal Faisal; Ami Amelia; Deri Islami; Nia Rahmadani Arman; Keiko Harsa Muhtadin; Vivi Mai Yarni; Rima Julia Sari (jurnal ABDIMAS Indonesia, 2025)
Non-communicable diseases (NCDs) are currently still the leading cause of death at the global level resulting in around 41 million deaths each year or almost equal to 7 out of 10 deaths that occur worldwide. PROLANIS (Chronic Disease Management Program) is a health service system and proactive approach implemented in an integrated manner involving Participants, Health Facilities and BPJS Health insurance in the context of health maintenance for BPJS Health participants suffering from chronic diseases to achieve optimal quality of life with effective and efficient health service costs. The high incidence of hypertension and cholesterol and the lack of knowledge of the use of BPJS health and the prolanis program in Melebung Village, so that this is the main problem that occurs in Melebung Village. The purpose of the activity is to increase community insight and knowledge about the Chronic Disease Management Program (PROLANIS). In this case the service team will provide education and assistance to the community regarding the BPJS Program (PROLANIS) and Herbal Medicine as an effort to prevent disease. The location of this activity will be carried out in one of the neighborhoods in Pekanbaru City, namely the Melebung Village neighborhood. The goal is that after this community service is carried out, it can improve the degree of public health through the BPJS Program (PROLANIS) and also increase community knowledge in the neighborhood regarding the use of family medicinal plants (herbal medicine).